Women and Society in Balochistan - Naudhani, Tahira (Al-Burz, 2010)
Our whole society is a multi-colored, which is strongly structured on the basis of gender specifications for both male and females. Our society has a rich heritage of socio-cultural diversity. Their inhabitants are admixture of different races. Balochistan society is basically tribal in nature and there are different ethnic group with their own patterns of socio-cultural system and code of conducts. There is a clear cut structural difference between rural and urban parts of the society. Balochsitani women have some special and significant characteristics as a member of a tribal society with some special features which increase the worth and dignity of a women and makes safer their position in a social system. Despite all these facts and realities, the Balochistani women is facing enormous hardships of life like poverty, illiteracy & ignorance and poor health conditions. Woman faces lack of social services and many other social problems and hurdles in their lives, but still she is fighting against all hardships with courage and consistency to combat the misfortunes to make their harsh destiny comfortable and prestigious.